Dynamics of a Class 1 Integron Located on Plasmid or Chromosome in Two Aeromonas spp. Strains - Pérez-Valdespino, Abigail; Lazarini-Martínez, Alfredo; Rivera-González, Alejandro X.; García-Hernández, Normand; Curiel-Quesada, Everardo (Frontiers in Microbiology, 2016)
Integrons are non-mobile bacterial genetic elements that carry different cassettes conferring antibiotic resistance. Cassettes can excise or integrate by action of an integron-encoded integrase, enabling bacteria to face environmental challenges. In this work the functionality and dynamics of two integrons carrying the same cassette arrangement (dfrA12-orfF-aadA2), but located on plasmid or chromosome in two different strains were studied. In order to demonstrate the functionality of the Class 1 integrase, circular cassette integration intermediaries were PCR amplified by PCR using extrachromosomal DNA extracted from bacteria grown in the presence or absence of cassette-encoded antibiotics. Circular aadA2 and dfrA12-orfF-aadA2 cassettes were detected in cultures grown either in the presence or absence of antibiotics in both strains. No dfrA12-orfF circular intermediates could be detected under any culture conditions. These results show that both integrons are functional. However, these elements show different dynamics and functionality since the presence of streptomycin led to detectable gene rearrangements in the variable region only in the strain with the plasmid-born integron. In addition, complete integration products were demonstrated using a receptor molecule carrying an empty integron. In this case integration products were observed in both strains even in the absence of antibiotics, but they were more evident in the strain with the plasmid-located integron when streptomycin was present in the culture medium. This suggests that integrons in the two strains respond differently to streptomycin even though DNA sequences upstream the intI1 gene, including the lexA boxes of both integrons are identical.